A geofilosofia da diferença de Gilles Deleuze e Félix Guattari - Asciutti, Luiz Roberto Rinaldi (2024)
This work purports to understand certain conceptual assemblages that Gilles Deleuze and Félix Guattari delimited on their philosophical road to produce a new field of thought, among which the determining relationships to elaborate and build an epistemological method connected to the intuition, a rhizomatic system of the singularities and a practical process of differentiation to constitute a new view to thinking. Therefore, the concepts of geophilosophy, difference and multiplicity are introduced to encompass the intensive flows necessary to building this new historic-philosophical terrain